HUBUNGAN ANTARA TINGKAT STRES TERHADAP TINGKAT NYERI DISMENOREA - Atiyatul Hikmah; Isti Antari; Tri Hardi Miftahul Ulum (Jurnal Kesehatan Madani Medika (JKMM), 2018)
Adolescence is time of storm and stress, stress is very vulnerable at the sixth-grade student, because of the thesis and some final exam which can trigger or exacerbate the occurrence of dysmenorrhea. This study aimed to determine the relationship of stress levels to dysmenorrhea levels on sixth grade student at D3 Midwifery Study Program of STIKes Madani Yogyakarta. The study design was descriptive analytic quantitative correlation using cross sectional approach. Sampling technique using total sampling, there were 31 respondents from 32 students who according to the criteria of inclusion. The independent variable is the level of stress and the dependent variable is the level of dysmenorrhea, to determine their relationships using Kendall's Tau test. Researchers obtained data using questionnaires Depression Anxiety Stress Scale (DASS) to measure level of stress and questionnaires Numeric Rating Scale (NRS) to measure the level of pain of dysmenorrhea. Student who suffered stress there are 93.5% and mostly on moderate stress, there are 45.1% and student who suffered dysmenorrhea pain there are as many as 96.7% most of them suffered mild dysmenorrhea pain 35.5%, while bivariate test using test kendall's tau, the results hypothesis test P = 0.000 (